Redefine the Concept of Play in Early Childhood Education - Dina Kusumanita Nur Alfaeni; Euis Kurniati (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
The concept of play is currently understood by teachers, but the practice of play in ECE is different and emphasizes calistung-oriented (reading, writing, and counting). Therefore, it is necessary to reflect on the concept of play by the teacher so that it can support early childhood play practice. The concept of play This article is aimed to explore the concept of play that ECE teachers understand through play pedagogy. This study uses a qualitative approach with a case study method through interviews and grounded theory analysis. The results of the study show that the teachers have an understanding of playing. However, in its implementation, the teachers consider several factors that cause learning to focus on activities to introduce reading, writing and counting. Factors influencing it include the teacher's academic qualifications and parents' demands. Parents demand that their children be academically successful and have calistung (reading, writing and counting) skills. So the concept of play for teachers is essential to support the calistung skills and early childhood development. Therefore, a teacher guidance program is needed to help teachers understand the implementation of play pedagogy in ECE. And the impact of this research is expected to be able to increase the pedagogical competence of teachers in restoring the nature of early childhood which cannot be separated from their playing activities.